2012
DOI: 10.1159/000345515
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Therapy for HCV-Associated Cryoglobulinemic Glomerulonephritis: Case Report and Review of the Literature

Abstract: We describe the case of a 51-year-old woman with HCV-associated cryoglobulinemic glomerulonephritis (GN). She presented mild deterioration of kidney function, non-nephrotic proteinuria, and active urinary sediment. Kidney biopsy showed features of membranoproliferative changes with some sclerosis. Sustained viral response (SVR) was obtained by 6 months of antiviral therapy (peg-IFN-α2a plus ribavirin). SVR was linked with improvement of kidney function and remission of proteinuria. Clinical and virological rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…By literature review, we found two case reports of patients with HCV-associated glomerulonephritis, presented with deterioration of kidney function and proteinuria. [17, 18] Treatment with INF-2a (one plus ribavirin) resulted in sustained virological response with a clinical remission of proteinuria as well as stabilization of renal function. Thus, we suggest that anti-virus therapy could ameliorate proteinuria in patients with HCV related glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…By literature review, we found two case reports of patients with HCV-associated glomerulonephritis, presented with deterioration of kidney function and proteinuria. [17, 18] Treatment with INF-2a (one plus ribavirin) resulted in sustained virological response with a clinical remission of proteinuria as well as stabilization of renal function. Thus, we suggest that anti-virus therapy could ameliorate proteinuria in patients with HCV related glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…However, especially when splenoma is present, as in our case, treatment with IFN alone might not be able to inhibit memory B cells. The complete remission rate of chronic HCV infection with IFN therapy is about 30% 31 . New therapeutic agents, such as protease inhibitors and polymerase inhibitors, have recently been developed and are expected to have beneficial effects 32 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The possibility has also been suggested that IFN aggravates primary glomerular diseases 31,35,36 . Previous reports indicate that in many cases of IFN-induced glomerulonephritis, remission was achieved by discontinuation of IFN therapy and appropriate treatment 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Severe adverse effects (fulminant hepatitis in HCV liver cirrhosis, serious infections, and sepsis) were rarely noticed when applied for primary glomerulonephritis treatment 26,38,41,42. Respiratory infections were slightly more frequent, as well as cytopenias, when rituximab was applied along with antiviral drugs 32,33,43. In some patients with HCV-related CryoVas, severe systemic reactions after administration of rituximab have been noticed 37,44.…”
Section: Safety Of Rituximab In Cryovasmentioning
confidence: 99%